Botanical Volatiles Selection in Mediating Electrophysiological Responses and Reproductive Behaviors for the Fall Webworm Moth Hyphantria cunea - Bai, Peng-Hua; Wang, Hong-Min; Liu, Bao-Sheng; Li, Min; Liu, Bai-Ming; Gu, Xi-Shu; Tang, Rui (Frontiers in Physiology, 2020)
Host-plant volatiles play vital roles for insects to locate foraging, mating, and oviposition sites in the environments. As one of the devastating invasive forestry pests, Hyphantria cunea is causing a great annual loss in China, and understanding its chemical ecology is an important task. The current research was done in terms of chemical analysis, electrophysiology, and behavioural assays on H. cunea to assess its olfactory reception towards host plant volatiles. A screen of possible common host volatiles was done targeting on 5 favored hosts of H. cunea, harvesting 6 potential bioactive compounds from a total of 78 odorant components. Six types of antennal sensilla were investigated on their distributions on the antennae, and sexual dimorphism was described. Hyphantria cunea showed responses to all selected host-related volatiles in electroantennogram tests, and linalyl butyrate elicited the strongest responses. Furthermore, mating rates in adult pairs which exposed to dibutyl phthalate and phytol have been significantly increased, while oviposition rates and female fecundity were not influenced. The results of the current study provide initial evidence showing that universal host-derived volatile cues are essential for H. cunena moth in terms of mating, which, can also provide insights into the development of botanical attractants.